1977
DOI: 10.1172/jci108720
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and phosphate transport in isolated segments of rabbit Henle's loop.

Abstract: A B S T R A C T Calcium and phosphate transport was examined in rabbit thin descending, thin ascending, and thick ascending limbs of Henle by in vitro perfusion of isolated tubular segments. Permeability coefficients for these segments with 45Ca and 32P04 were determined for both lumen-to-bath and bathto-lumen directions. Both the thin descending and thin ascending limbs were found to be relatively impermeable to both 45Ca and 32PO4. In neither segment were we able to show evidence for net transport of calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(44 citation statements)
references
References 24 publications
4
40
0
Order By: Relevance
“…The basement membrane of the thin limb appears an unlikely site for initial crystallization in patients with idiopathic hypercalciuria. It is not the site of either vectorial calcium or phosphorus transport (8) and, since even the transtubular permeabilities of these ions are very low (8), it is difficult to link supersaturation within the thin limbs (9) to the surrounding interstitium. However, anatomically, the thin limbs are in very close proximity to the vasa recta and the collecting ducts, and all are situated in a highly concentrated, hypertonic environment.…”
Section: Potential Mechanisms For Stone Formationmentioning
confidence: 99%
“…The basement membrane of the thin limb appears an unlikely site for initial crystallization in patients with idiopathic hypercalciuria. It is not the site of either vectorial calcium or phosphorus transport (8) and, since even the transtubular permeabilities of these ions are very low (8), it is difficult to link supersaturation within the thin limbs (9) to the surrounding interstitium. However, anatomically, the thin limbs are in very close proximity to the vasa recta and the collecting ducts, and all are situated in a highly concentrated, hypertonic environment.…”
Section: Potential Mechanisms For Stone Formationmentioning
confidence: 99%
“…Calciuim absorption in the loop of Henle had been attributed to the thick ascending limb, and recent isolated tubule microperfuisioin studies have confirmed the presence of significant calcium transport in this segment (2)(3)(4).…”
mentioning
confidence: 95%
“…11 The luminal transepithelial potential difference in TAL that promotes paracellular uptake of Ca and Mg is coupled to the activity level of NKCC2. [12][13][14] (3) Urinary excretion of K is lower in blacks than in whites. 15 Greater Na uptake anywhere in proximal nephron regions, including TAL, would result in suppression of aldosterone levels, as well delivery of less Na downstream, both causing a reduction in distal nephron function, which is coupled to K secretion.…”
mentioning
confidence: 99%